From Physical Space to Digital Systems: Repositioning Government Office Functions in the Era of Automation - Mirelle Gavania Addiba; Rhesyakha Syadza Syach (Asosiasi Ahli Administrasi Indonesia, 2026)
Digital transformation changes the function and role of government offices from an administrative center to a digital-based center for data integration and cross-unit coordination. This study aims to evaluate the effectiveness of digital government coordination in the city of Bandung and provide recommendations for repositioning the role of offices in the era of automation. With a descriptive literature study method that utilizes academic literature sources, reports from various agencies, and the results of previous research, an overview of digital coordination in various local governments is obtained. The results show that the use of integrated systems such as the Bandung Command Center (BCC) and the Bandung City Government Integrative Data Analytics System (SADIG) improves efficiency, transparency, and accuracy of communication and decision-making. However, its effectiveness is still limited by limited interoperability, low digital literacy of apparatus, and lack of optimal data governance. This study recommends repositioning the role of the office as a data governance center and collaboration facilitator through the establishment of a Data Integration and Collaboration Office unit, strengthening interoperability between SKPDs, and increasing data analysis capacity. The novelty lies in the concept of the office as a data governance manager and digital coordination center that is adaptive to automation.